Post-collision interaction effect in THz-assisted Auger decay of noble gas atoms. (3rd May 2021) - Bermúdez Macias, I J; Düsterer, S; Ivanov, R; Frühling, U; Kabachnik, N M
Abstract: Auger electron spectra were simulated in the presence of a terahertz streaking field to study post-collision interaction (PCI) effects in the time-evolution of photoinduced Auger decays. The PCI is characterized by the ratio of the spectral line width for Auger electron emission in opposite directions with respect to the THz-field. These calculations have been performed using the analytical semiclassical model developed by Bauch and Bonitz (2012 Physical Review A 85 053416). The results are shown for Ne(KLL), Ar(LMM), Kr(MNN) and Xe(NOO) Auger transitions whereby different possible experimental conditions were evaluated.